At Midnight I Rise: The Symbolism of Midnight in the Assertion of Jewish-Christian Difference - Polyakov, Emma O'Donnell 1977- (2024)
, precis:, This essay explores the negotiation of Jewish-Christian difference in the beginning of the Common Era through a comparative study of the symbolic associations of midnight. It comparatively analyzes references to midnight in the Hebrew Bible and the New Testament, as well as their later reception in Jewish and Christian communities, with attention to how the early Christian community adopted Jewish traditions of time and revised them to reinforce emerging Christian concepts. This essay proposes that the divergent symbolic associations of midnight in the two canons illustrate some of the central concerns and self-understandings of early Christian and Jewish communities, which became thematic in the assertion of Jewish-Christian difference during the parting of the ways. It demonstrates that the midnight passages are thematically linked as a time of transformation, but the content of that transformation differs between the two canons, reflecting themes of concern to the communities that developed the texts. Across the passages in the Hebrew Bible, midnight appears to be symbolic of a transformation that leads to the creation or strengthening of the people of Israel. In contrast to the national transformation envisioned in the Hebrew Bible, references to midnight in the New Testament are thematically related in their presentation of midnight as a time of eschatological transformation, symbolizing the turning point from this world to the next world, and reflecting an emerging religious tradition focused on a redemption beyond worldly time. This essay argues that these distinct thematic associations present concepts of transformation that were asserted during the parting of the ways, as the two religious traditions formulated parameters around their identities. It concludes with an exploration of two distinct temporal visions that eventually emerged as the two traditions separated, drawing parallels between the literary symbolism of midnight in the biblical text and later developments in Jewish and Christian perspectives on time.